2009
DOI: 10.1186/1744-8069-5-70
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Immune Responses and Macrophage/Neuron Interactions in the Dorsal Root Ganglion in Young and Adult Rats following Nerve Injury

Abstract: BackgroundNeuropathic pain is an apparently spontaneous experience triggered by abnormal physiology of the peripheral or central nervous system, which evolves with time. Neuropathic pain arising from peripheral nerve injury is characterized by a combination of spontaneous pain, hyperalgesia and allodynia. There is no evidence of this type of pain in human infants or rat pups; brachial plexus avulsion, which causes intense neuropathic pain in adults, is not painful when the injury is sustained at birth. Since i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 82 publications
6
110
1
2
Order By: Relevance
“…Interestingly, 5-HT 2B R-positive macrophages are predominantly localized around large cell bodies that are presumably responsible for mechanical transduction. This distribution of macrophages has already been described [60] and a clear relationship was observed between tactile allodynia and macrophage infiltration [16].…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, 5-HT 2B R-positive macrophages are predominantly localized around large cell bodies that are presumably responsible for mechanical transduction. This distribution of macrophages has already been described [60] and a clear relationship was observed between tactile allodynia and macrophage infiltration [16].…”
mentioning
confidence: 66%
“…Intrathecal injections were performed under volatile anesthesia (see next paragraph). We injected 20 µl (30,60, 125 ng RS127445) of the antagonist or vehicle directly through the intact skin, between the L5 and L6 vertebrae, with a Hamilton syringe equipped with a 26-gauge needle. We applied 10 µl of solution (125 ng) to the sciatic nerve, as described below.…”
Section: Animals and Ethics Statementsmentioning
confidence: 99%
“…Indeed, a recent study showed that following nerve injury a very high level of transcriptional activity occurs in adult rat DRGs but not in younger ones. Our observations suggest that the different pattern of mRNAs in the axons of DRG neurons of adult and young rats might be instrumental in the postnatal developmental of neuropathic pain (Vega-Avelaira et al 2009). The DRGs in our experiments were grown in the presence of NGF to maintain neuronal viability.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the levels of the β-catenin and menin proteins, which are involved in the formation of new synapses (25), and the number of neurons reacting to the Aβ-fiber stimulation (26) are increased in lamina II of the spinal dorsal horn of SNI rats. In dorsal root ganglia (DRG), macrophages form clusters around the cell bodies of A-fibers, but not small C-fibers, in the SNI model (27). These changes in spinal cord neurotransmission after SNI surgery may contribute to mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%